TINJAUAN YURIDIS PIDANA MATI TERHADAP TINDAK PIDANA TERORISME PERSFEKTIF HAK ASASI MANUSIA - Lestari, Fuji; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Criminal law is the norms that contain the necessities and prohibitions which the legislators formhave been associated with a sanction in the form of punishment, namely a special suffering. Criminal is asentence imposed on someone who is proven legally and convincingly commits a crime. In evidence ofteninterpreted as an effort to foster his personality in accordance with the values in society and culture. The deathpenalty is considered as a punishment that makes a deterrent effect for a crime. In Human Rights a set of rightsthat are inherent in the nature and existence of human beings as the supreme godhead and are a gift that mustbe respected, at the highest end and protected by the State, law and government, and every person for honorand protection of dignity human. Based on this understanding the writer of this thesis formulates twoformulations of the problem, namely: first, What are the views and perspectives of criminal law and humanrights in Indonesia on the implementation of capitalism perpetrators of terrorism, Second What is the basis forconsidering justifiers of criminal sanctions against terrorism.In the results of the problem research there are two main things that can be concluded. First, thecontradictory view of the application of the death penalty (abolitionist) in Indonesia. Meanwhile, the view thatis pro-retentionist assumes that capital punishment must still be maintained and applied only to extraordinarycrime such as terrorism, to applied by this group considers that the death penalty will provide a deterrenteffect, so that it will prevent the recurrence of similar crimes by other people. See again from the view ofhuman rights. The two basic considerations for justifying the death of law for terrorism are three, in terms ofsociological, ideological, philosophical juridical.Keywords: Crime, Views of Death Penalty, Terrorism, Human Rights